Gambaran morbiditas bayi dengan berat badan Lahir rendah (bblr) di ruang perinatologi Rsud arifin achmad pekanbaru - Syafrida - Hanum; Oswati - Hasanah; Veny - Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aimed of this research was to determine the morbidity of Low Birth Weight (LBW) infants in Perinatology unit at Arifin Achmad General Hospital. This study used a descriptive design with retrospective study approach. The samples in this research were 509 medical records of LBW infants taken by purposive sampling method. Univariate analyse was used and it showed that majority of LBW (84.9%) had low birth weight category (1501-2500 gram), 70.7% had a gestational age less than 38 weeks, and mean value of length of stay were 15.81 days for infants with complex morbidity. The result showed that majority of LBW infants had a complex morbidity (74.1%). According to this result, it is recommended for giving health promotion about antenatal care to pregnant women and also preparing the equipment and health provider to completely handle the cases of morbidity in LBW infants.